The EU Carbon Border Adjustment Mechanism and its Influence on Steel Imports from Taiwan - Frank Best (ZBW - Leibniz Information Centre for Economics, 2023)
In order to avoid carbon leakage, the EU decided to introduce the Carbon Border Adjustment Mechanism to put a fair price on embedded carbon emissions of products imported into the EU. Once the CBAM is operational, importing companies will have to declare the embedded emissions for their products and surrender the corresponding amount of CBAM certificates. Taiwan is an important trade partner of the EU, especially for electronic components, and also for base metals like Iron & Steel or Aluminium. The industrial manufacturing for base metals yields high Scope 1 greenhouse gas emissions; additionally, power generation in Taiwan relies heavily on fossil fuels. This paper identifies the Iron & Steel product flows from Taiwan to the EU. It describes the CBAM requirements and the potential impact on Taiwanese Iron & Steel exports, pointing out challenges and opportunities. It intends to support Taiwanese companies to prepare for CBAM rules both during the transition phase and once the system is fully active. – – Um Carbon Leakage zu vermeiden, beschloss die EU den Carbon Border Adjustment Mechanism (CBAM) als Grenzausgleichsmechanismus einzuführen, um CO2-Emissionen von Produkten, die in die EU importiert werden, fair zu bepreisen. Sobald der CBAM funktionsfähig ist, müssen importierende Unternehmen die entstandenen Emissionen für ihre Produkte deklarieren und die entsprechende Menge an CBAM-Zertifikaten abgeben. Taiwan ist ein wichtiger Handelspartner der EU, insbesondere für elektronische Komponenten, aber auch für Grundstoffe wie Eisen & Stahl oder Aluminium. Die industrielle Herstellung dieser Produkte führt zu hohen Scope-1-Treibhausgasemissionen; zusätzlich basiert die Stromerzeugung in Taiwan stark auf fossilen Brennstoffen. Dieses Papier identifiziert die Importströme von Eisen & Stahl von Taiwan in die EU. Es beschreibt die Anforderungen des CBAM und die potenziellen Auswirkungen auf die Exporte von taiwanesischem Eisen & Stahl und zeigt Herausforderungen und Chancen auf. Es zielt darauf ab, taiwanesische Unternehmen dabei zu unterstützen, sich sowohl während der Übergangsphase als auch nach der vollständigen Inbetriebnahme des Systems auf die CBAM-Regeln vorzubereiten.
Conference: The 19th International Conference on Knowledge-based Economy and Global Management. Tainan, Taiwan, 2-3 November, 2023
Keywords: F14; H23; M16; L61; 330; CBAM; Carbon Border Adjustment Mechanism; Emission Intensity; Emission Trading Scheme; EU-ETS; Imports; Iron; Steel; Taiwan; TSCE